Transfer of Knowledge and Forgetting in Islamic Religious Educational Psychology - Faisal Amir Toedien; Muslim Afandi; Mhd Subhan (Da'wa Faculty of Islamic State University Salatiga, 2025)
This study aims to examine the phenomenon of learning transfer and forgetting within the context of Islamic Religious Education from the perspective of educational psychology. A qualitative method was employed, utilizing a literature review approach to analyze relevant theories related to learning, memory, and the process of forgetting. The data were analyzed using content analysis techniques based on scientific sources discussing the concepts of learning transfer and forgetting, along with their implications for Islamic Religious Education instruction. The findings indicate that learning transfer often fails due to rote-based, less meaningful, and non-contextual learning approaches. Meanwhile, forgetting occurs due to a lack of reinforcement, the material's minimal relevance to students' real-life experiences, and interference from other information. The study concludes that to enhance the effectiveness of Islamic Religious Education learning, educators should implement strategies that emphasize meaningful comprehension, repeated reinforcement, and contextual linkage between the material and students' daily lives, thereby optimizing learning transfer and minimizing the likelihood of forgetting.